Third component of human complement: Localization of the internal thiolester bond - Thomas, Matthew L. (1982)
Human complement protein C3 was inactivated by using methylamine and thereby generating a SH group from the internal thiol ester. The protein was coupled via this SH group to activated thiol-Sepharose and digested with elastase. Fragment C3d remained attached to the thiol-Sepharose and was subsequently eluted with L-cysteine. Concomitantly, the original SH group was regenerated, and it was then labeled with iodo[2-(3)H]acetic acid. Partial sequence analysis of the radiolabeled C3d fragment showed that both components of the thiol ester are located close to the amino terminus (residues 23 and 26). Specific chemical cleavage of the α-chain was achieved after S-cyanylation of the thiol. The two fragments obtained corresponded to the amino-terminal section (M(r) ≈46,000) and the carboxy-terminal section (M(r) ≈70,000). These results together indicate that fragment C3d occupies approximately positions 345-610 of the α-chain. The partial sequence of C3d was extended by completion of the sequence of a previously described tryptic peptide. Comparison of residues 1-49 of C3d with a peptide from α(2)-macroglobulin [Swenson, R. P. & Howard, J. B. (1980) J. Biol. Chem. 255, 8087-8091] shows a previously recognized identity of seven residues around the thiol ester site and a second region of identity around a known glycosylation site of α(2)-macroglobulin. The relationships among these proteins and protein C4 are discussed. An overall outline of the structure of C3 is presented, showing the locations of various fragments and cleavage sites. The thiol ester group places constraints on the local folding of the peptide chain; a possible conformation is suggested and discussed in relation to the mechanism of activation.